The Role of Hope in Learning and Academic Success - Khpalwak, Mohammad Tahir (Journal of Social Sciences - Kabul University, 2021)
Academic life is one of the most critical aspects of human development. Success and satisfaction in education are indicators of human progress and purposefulness. One of the factors that negatively affect academic performance in students, particularly those in schools and universities, is academic frustration. Hope is defined as having a positive expectation of achieving one's goals. This review-analytical study examines the role of hope in learning and academic success, drawing upon previous research. Findings indicate that hope is fundamental to mental well-being and is a basic necessity for students. Moreover, hope is positively correlated with high academic performance and achievement. Encouraging hope in students plays a crucial role in their educational success.